(untitled) (Journal of human and social sciences, 2023)
This study aims to highlight the impact of administrative factors, specifically organizational factors and administrative planning, on the delay in establishing a new city as a solution to the crisis of overpopulation in Benghazi, the economic capital. The research examines the role of the Urban Development and Cities Authority in this delay due to the insufficient application of organizational factors. The study adopted a descriptive-analytical approach, with data collected through a questionnaire distributed to 35 employees, including engineers, section heads, and department directors. Findings revealed that poor planning, resulting from weak organizational factors (information, competencies, financing, legislation, and technology), was a key cause of the delay. The results also showed a moderate level of support from top management for various planning stages (identification, goal setting, data collection and analysis, preparing and selecting alternatives, drafting plans, and implementing and monitoring). The study concludes with recommendations to secure financial resources and attract qualified professionals, as well as to enhance employees’ motivation for innovation and creativity by providing a supportive work environment, thereby accelerating the establishment of a new city to reduce the burden on Benghazi. Keywords: New city, Organizational factors, Planning.